Chemical reaction and Newtonian heating effects on steady convection flow of a micropolar fluid with second order slip at the boundary - Kamran, Muhammad; Wiwatanapataphee, Benchawan (2018)
© 2018 Elsevier Masson SAS. In this paper, asymptotic analysis of the chemical reaction and the Newtonian heating parameters is carried out. A mathematical model of a convective micropolar fluid flow over a permeable stretching/shrinking sheet is taken into account in the presence of the slip flow regime. A nonlinear system of transformed equations is solved by a semi-analytical technique called Homotopy Analysis Method (HAM). The current investigation is in a good agreement with the already published analytical and the numerical results with the help of tabular and graphical representations. In comparison with the stretching sheet, it is observed that the shrinking sheet produces a wider concentration boundary layer thickness by a small change in the chemical reaction parameter. In contrast to the stretching sheet, the Newtonian heating parameter raises the thermal boundary layer thickness by 39.93% for the shrinking sheet. The chemical reaction with the Newtonian heating effect is an important consideration in the solidification process of the liquid crystals and the polymeric suspensions.